Analisis Peran Guru Dalam Mengatasi Kenakalan Verbal Siswa Di SDN 1 Limboto Kabupaten Gorontalo - Vuvut Karim; Abd Hamid Isa; Yurni Rahman (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the role of teachers in addressing students’ verbal misconduct at State Elementary School 1 Limboto, Gorontalo Regency. The study involved 10 informants consisting of the principal, 3 homeroom teachers (grades IV, V, VI), and 6 studentsd. This research employs a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, teachers, and students as informants. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that forms of verbal misconduct found include mocking peers, using inappropriate language, interrupting conversations, and chatting during the learning process. The factors causing students’ verbal misconduct originate from both internal and external aspects, such as lack of parental attention, social environmental influences, and weak supervision and character development. The role of teachers in addressing verbal misconduct is implemented through providing role models, character building, persuasive approaches, positive reinforcement, and collaboration with parents and the school. With consistent and collaborative teacher involvement, verbal misconduct can be minimized, and a conducive learning environment can be established.